PENGARUH PENAMBAHAN GEL LIDAH BUAYA (Aloe vera L.) TERHADAP RASA DAN AROMA BAKSO DAGING SAPI - Rista Aprilia Putri; Doso Sarwanto; Susilo Rahardjo; Yanita Mutiaraning Viastika (MEDIA PETERNAKAN, 2024)
This research aims to determine the effect of the percentage of addition of aloe vera gel on the taste and aroma of beef meatballs. This research was carried out from 22 April 2024 to 23 April 2024 at the Laboratory of the Faculty of Animal Husbandry, Wijayakusuma University, Purwokerto. The ingredients used in this research include: beef, tapioca flour, ice cubes, garlic, pepper, table salt and aloe vera gel. This research used a Completely Randomized Design (CRD) with a unidirectional pattern with 4 treatments, the amount of aloe vera gel P0=0%, P1=5%, P2=10%, P3=15% which will be added to 500 grams of ground beef in each treatment. The variables measured were taste and aroma using 25 semi-trained panelists. The results of the variance analysis stated that the addition of aloe vera gel was different but not significant (P>0.05) to the taste of beef meatballs and very significantly different (P<0.05) to the scent of beef meatballs. The conclusion of this research is that the percentage of adding aloe vera gel to beef meatballs does not affect the taste of the meatballs but does affect the aroma of the meatballs. The higher the percentage of aloe vera gel, the more pleasant the scent.